A Research on Level of Loneliness Among Female and Male Students Studying Professional Courses - Pratima, Km; Mahananda, Manju (South Asian Journal of Social Sciences and Humanities, 2021)
The aim of this study was to analyze the level of loneliness among females and males studying professional courses. We measured the Level of Loneliness between female and male university students studying professional courses (N=80). Professional courses pursuing women and men were between the age group of 19-22 years. Results reveals that females pursuing professional courses were more in number in the high loneliness category when compared to professional courses pursuing males, which is significantly related to loneliness. This result supports the belief that family and society play an integral role in defining and influencing the profession, and that loneliness is indirectly connected to relationships. Finally, correlation analysis indicated positively between youth: female and male. It is proposed that daily therapy should generally be given to professional young people who have issues with loneliness.